PENGARUH CORPORATE GOVERNANCE, ARUS KAS BEBAS DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Samuel Braindies A. S; Fuad Fuad (Diponegoro Journal of Accounting, 2019)
This study aims to analyze and provide empirical evidence of the influence of the implementation of corporate governance mechanisms on earnings management at manufacturing companies listed on the Indonesia Stock Exchange. The independent variables used are corporate governance represented by free cash flow,leverage, profitability, audit committee, board of directors, board of independent comissioners while the dependent variable used is earnings management. The populations in this study are manufacturing companies listed on the Indonesia Stock Exchange in the period 2015-2017. The sample of this study consists of 255 companies listed in Indonesia Stock Exchange. The data that was used in this study was secondary data and sample selection using purposive sampling method. The analysis model uses multiple linear regression analysis. Based on the results of the analysis shows that the variable of free cash flow has a negative effect on earnings management, and the hypothesis is accepted. Variable leverage, profitability, audit committee, board of directors, board of independent comissioners have no significant effect on earnings management.